Informed Consent in Occupational Health Research: A Review on Ethical Challenges - Andrias Norris (ILUNI MKK FKUI and PRODI MKK FKUI, 2025)
Background: In research involving human subjects, including occupational health research, informed consent must be obtained from prospective participants. However, the extent to which informed consent should be obtained, what should be disclosed to participants, and how the process should be conducted are not always given due consideration in research. Methods: In April 2025, we conducted a journal search using basic techniques across all sources on Google, Google Scholar and Scopus. We also searched PubMed using advanced search techniques and medical terms (MeSH terms). The journals were published in English at any time between 2014 and 2025.Results: In a study involving human subjects, ethical principles must be followed. One of these principles is obtaining informed consent from potential participants. No one, including the state, can force someone to participate in research, and participants can withdraw from the study at any time. Researchers must obtain informed consent from potential participants. The principle of informed consent requires information, understanding and voluntariness to be fully upheld, ensuring that participants are fully aware of the research being conducted and thereby ensuring the validity of the research results. In certain cases, informed consent may be modified or waived with the approval of the research ethics committee.Conclusions: Researchers can learn about the important role of informed consent in research involving human participants, including those involved in occupational health studies. If prospective participants do not understand the informed consent process, this can cause research to become biased or even lead to withdrawal from the research process. In addition to complying with the three principles of informed consent (information, understanding and voluntariness), the consent process must also take into account the appropriate format, which should be concise and focused.